Short Communication: Analysis of weed vegetation in immature and mature oil palm plantations - Halus Satriawan; ZAHRUL FUADY (Society for Indonesian Biodiversity, 2019)
Abstract. Satriawan H, Fuady Z. 2019. Analysis of weed vegetation in immature and mature oil palm plantations. Biodiversitas 20: 3292-3298. The species of weeds which grow and dominate in palm oil areas depend on location, local climate, and the light received. This research aimed to determine the diversity of weeds in the planting of palm oil with a different age grown in 2012, 2013, 2014 and 2016. The sample slots measured uniformly at 1 m x 1 m totaling 25 plots. Vegetation analysis was conducted to the density (D), relative density (RD), frequency (F), relative frequency (RF), important value index (IVI), Summed Dominance Ratio (SDR), and Species Diversity Index (H’). Weed composition includes 21 families with 36 species, with the total number of each individual during the year of palm oil planting was 3540, 3148, 3731, and 2910. The relative density value of the highest weeds in the planting year group in 2012 and 2013 were Asystasia intrusa (20.22% and 21.05%), in 2014 were Eleusine indica (23.93%) and 2016 were Cynodon dactylon with 24. 49%. The importance value of weeds in four groups in planting year of oil palm was also in line with the relative density value. These were A. intrusa in 2012 and 2013, amounting to 27.41 and 27.95 and in 2014 and 2016, totaling to 23.72 and 37.64 was E. indica and C. dactylon. The value of the highest species diversity of 6.85 was found in the year 2014, followed by 2012 with 5.88.